PENGARUH SELF-EFFICACY DAN DUKUNGAN SOSIAL TERHADAP HASIL BELAJAR MAHASISWA - Hermin Arista (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The goal of this study is to see how self-efficacy and social support affect student learning results. This is an ex-post facto study with a quantitative design and a causal character. A sample of 28 students was employed in this study. This study includes both independent and dependent variables. Self-efficacy (X1) and social support (X2) are the independent variables, whereas learning results (Y) are the dependent variable. The IBM SPSS Statistics 23 tool is used for data analysis, which employs multiple linear regression data analysis.The research findings indicate that (1) self-efficacy has a significant influence on the learning outcomes of Electrical Engineering students at Panca Marga University, Probolinggo, (2) social support has a significant influence on the learning outcomes of Electrical Engineering students at Panca Marga University, Probolinggo, and (3) self-efficacy and social support together have a significant influence on the learning outcomes of Electrical Engineering students at Panca Marga University, Probolinggo. The size of the influence of student self-efficacy and social support is 61.6%, with other variables influencing 38.4%. This suggests that student learning results are strongly influenced by self-efficacy and social support.